Mechanistic Studies of the Antiallergic Activity of Phyllanthus amarus Schum. & Thonn. and Its Compounds - Nur Zahirah Abd Rani; Kok Wai Lam; Juriyati Jalil; Hazni Falina Mohamad; Mohd Shukri Mat Ali; Khairana Husain (Molecules, 2021)
Phyllanthus amarus Schum. & Thonn. (Phyllanthaceae) is a medicinal plant that is commonly used to treat diseases such as asthma, diabetes, and anemia. This study aimed to examine the antiallergic activity of P. amarus extract and its compounds. The antiallergic activity was determined by measuring the concentration of allergy markers release from rat basophilic leukemia (RBL-2H3) cells with ketotifen fumarate as the positive control. As a result, P. amarus did not stabilize mast cell degranulation but exhibited antihistamine activity. The antihistamine activity was evaluated by conducting a competition radioligand binding assay on the histamine 1 receptor (H1R). Four compounds were identified from the high performance liquid chromatography (HPLC) analysis which were phyllanthin (1), hypophyllanthin (2), niranthin (3), and corilagin (4). To gain insights into the binding interactions of the most active compound hypophyllanthin (2), molecular docking was conducted and found that hypophyllanthin (2) exhibited favorable binding in the H1R binding site. In conclusion, P. amarus and hypophyllanthin (2) could potentially exhibit antiallergic activity by preventing the activation of the H1 receptor.